Gene therapy in oral cancer: a promising prospect - Arief Ichwan, Solachuddin Jauhari (2016)
Oral squamous cell carcinoma (SCC) is the most frequently occurring malignant tumor of the oral cavity with poor prognosis resulting in major morbidity and mortality. The incidence of oral SCC is increasing in developing countries including Indonesia. Modifications of conventional cancer therapies, including surgery, radiotherapy, and chemotherapy, have not improved the survival rates of patients oral cancer. Even, tumors recur in approximately one third of patients which mainly lead to severe morbidity. The recurring cancer is often considered incurable since majority of cases; palliative surgery is disfiguring and more complicated, whereas some tumors have become resistant to either chemotherapy or further radiotherapy. For this reason, gene therapy has been developed and considered as a new approach that may effective in combating cancers. Gene therapy can be defined as the treatment of disease by replacing, altering, or supplementing a gene that is absent or abnormal and whose absence or abnormality is responsible for a disease. Like any other type of cancers, oral cancer cells harbor genetic mutations which resulting in failures to restrict or control the cell growth. Although still in its early stages, gene therapy holds great promise for the treatment of oral cancer. This review will attempt to discuss the principles and methods of gene therapy especially those utilized for treatment of oral cancer. The ongoing clinical trials that are being conducted also will be summarized.